2021
DOI: 10.3390/nu13061960
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine Sources and Consumption among Saudi Adults Living with Diabetes and Its Potential Effect on HbA1c

Abstract: Information regarding the spread and effect of coffee and caffeine intake by individuals with type II diabetes remains unclear. This study aims to identify the amount and sources of habitual caffeine intake by individuals with type II diabetes and to investigate its association with other health outcomes, especially HbA1c. This is a cross-sectional survey involving 100 people medically defined as having type II diabetes comprising both genders, recruited from a care centre. All participants completed a caffein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Concerning caffeine consumption, coffee remains the primary source of caffeine intake, which corroborates the results in most European countries and the United States of America [ 7 , 19 , 21 , 22 ]. Approximately two billion coffee “express” are estimated to be consumed every day in the world [ 23 ]. Other caffeine sources consumed are sodas, energy drinks, tea, chocolate drinks, food (i.e., chocolate, yogurt, ice cream, candies, and baked food), food supplements, and over-the-counter drugs (although some products had little expression in the present study) [ 1 , 5 , 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Concerning caffeine consumption, coffee remains the primary source of caffeine intake, which corroborates the results in most European countries and the United States of America [ 7 , 19 , 21 , 22 ]. Approximately two billion coffee “express” are estimated to be consumed every day in the world [ 23 ]. Other caffeine sources consumed are sodas, energy drinks, tea, chocolate drinks, food (i.e., chocolate, yogurt, ice cream, candies, and baked food), food supplements, and over-the-counter drugs (although some products had little expression in the present study) [ 1 , 5 , 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18] A number of cross-sectional studies showed that females in Saudi Ariba prefer and consume more caffeine (mainly Arabic coffee) than males which is similar to our results where females represent (80%) of the participants. [14,16] On the other hand, undergraduate students represent most of the participants in our study (85%), and they may be at an increased risk of excessive caffeine consumption due to seeking On the other hand, the use energy drinks, consumed by 17% of participants in our study, has been increasing dramatically in the last two decades, and Saudi Arabia is not an exception. Companies are actively pushing advertising, sponsorship of sporting events and massive subsidies to retailers that sell them.…”
Section: Discussionmentioning
confidence: 93%
“…[12][13] Information regarding the spread of the different types of coffee and caffeinated products consumed by the Saudi population remains unclear. [14] This study aims to identify the amount and sources of caffeine consumed by the Saudi population and explore its relationship with the consumption patterns. This is to provide public health practitioners and dietitians with information on caffeine consumption, to help them understand the situation and make suitable recommendations for patients.…”
Section: Introductionmentioning
confidence: 99%
“…The Saudi population has unique dietary behaviors that are significantly different from those of Western and East-Asian populations. For example, the literature has shown a high prevalence of beverage consumption among Saudi people [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%